EVALUATION OF ANTIBIOTIC USE IN PNEUMONIA PATIENTS USING THE ATC/DDD METHOD AS A FORM OF SHARIA IMPLEMENTATION AT TUGUREJO REGIONAL HOSPITAL, SEMARANG CITY IN 2024 - Sabtersi, Allisia; Ramadhani, Azmi; Mutiarawati (SAINS INDONESIANA, 2025)
Pneumonia is an infectious disease of the lower respiratory tract that causes mortality and morbidity in hospitals. Common symptoms of pneumonia are fever, chills, headache, cough with phlegm and shortness of breath (Apriliany et al., 2022). Pneumonia causes acute inflammation of the lung tissue (alveoli) caused by bacteria, viruses, fungi, or parasites (Salasanti et al., 2024). Pneumonia can be prevented by using antibiotics. Inappropriate use of antibiotics can cause antibiotic resistance. So it is necessary to control the use of antibiotics by conducting a quantitative evaluation. The purpose of this study was to determine the profile of antibiotic use and the quantity of antibiotic use in pneumonia patients at Tugurejo Hospital in Semarang City in 2024 calculated by the ATC/DDD method. This study is an observational study with a retrospective cross-sectional design using medical record data of pneumonia patients hospitalized at RSUD Tugurejo Semarang City.